Implementation of Central Government Policy on Priority for the Use of Village Funds in Makartitama and Ulak Mas Villages, Lahat Regency, Indonesia - Heru Purnawan (Department of Public Administration, Universitas Negeri Surabaya, 2021)
This study aims to analyze the implementation of Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration of the Republic of Indonesia (Kementerian Desa, PDT, dan Transmigrasi) Number 11 of 2019 concerning Priorities for the Use of Village Funds in 2020, in Makartitama Village and Ulak Mas Village, Lahat District, Lahat Regency. This Ministerial Regulation stipulates that the priority of using village funds must provide maximum benefit to the village community in the form of improving life quality, increasing welfare, poverty alleviation, and accelerating public services. Unfortunately, the situation of each village is varied, that is, the policy implementation needs further investigation. The present study used a qualitative research method. The focus was the implementation aspects such as the compliance level of the implementor, how routine functions ran, and performance and impact. Data were collected using interviews and policy documents analysis. The findings showed that the Minister's policy could not be fully implemented. Of the four priorities, only three aspects were implemented. The priority that had not been implemented was the program to improve public services. The socio-economic situation of the community was the main reason for the village government to focus more on the first three priorities, namely improving life quality, improving welfare, and alleviating poverty. The external aspect that affected the implementation of this regulation was the budget reduction from the central government due to the impact of the Corona Virus Disease 2019 (Covid-19) Pandemic. This study suggests the need for an in-depth evaluation of prioritizing the use of the village budget by considering the local needs. There is the need for anticipatory steps to deal with force major conditions such as Covid-19 that reduces the amount of village fund allocations and affects the implementation of village programs. Abstrak Penelitian ini bertujuan untuk menganalisis pelaksanaan Peraturan Menteri Desa, Pembangunan Daerah Tertinggal, dan Transmigrasi Republik Indonesia Nomor 11 tahun 2019 tentang Prioritas Penggunaan Dana Desa tahun 2020, di desa Makartitama dan Desa Ulak Mas, Kecamatan Lahat, Kabupaten Lahat. Peraturan Menteri tersebut mengatur bahwa prioritas penggunaan dana desa harus memberikan manfaat sebesar-besarnya bagi masyarakat desa berupa peningkatan kualitas hidup, peningkatan kesejahteraan, pengentasan kemiskinan, dan percepatan pelayanan publik. Sayangnya, situasi masing-masing desa sangat beragam, sehingga implementasi kebijakan perlu diselidiki lebih lanjut. Penelitian ini menggunakan pendekatan penelitian kualitatif. Fokusnya adalah aspek implementasi seperti tingkat kepatuhan implementor, bagaimana fungsi rutin dijalankan, serta kinerja dan dampaknya. Pengumpulan data dilakukan dengan menggunakan wawancara dan studi dokumen. Hasil penelitian menunjukkan bahwa kebijakan Menteri tersebut belum dapat dilaksanakan sepenuhnya. Dari empat prioritas tersebut, hanya tiga aspek yang dilaksanakan. Prioritas yang belum terlaksana adalah program peningkatan pelayanan publik. Situasi sosial ekonomi masyarakat menjadi alasan utama pemerintah desa untuk lebih fokus pada tiga prioritas pertama, yaitu peningkatan kualitas hidup, peningkatan kesejahteraan, dan pengentasan kemiskinan. Aspek eksternal yang mempengaruhi penerapan peraturan ini adalah pengurangan anggaran dari pemerintah pusat akibat dampak Pandemi Corona Virus Disease 2019 (Covid-19). Kajian ini menyarankan perlunya evaluasi mendalam dengan memprioritaskan penggunaan anggaran desa dengan mempertimbangkan kebutuhan lokal. Aspek penting lainnya adalah perlunya langkah antisipatif untuk menghadapi kondisi force major seperti Covid-19 yang mengurangi jumlah alokasi dana desa dan mempengaruhi pelaksanaan program desa. Kata kunci: implementasi kebijakan, dana desa, prioritas dana desa